Pengembangan Media Film Pendek “ASA” sebagai Upaya Pencegahan Kekerasan Seksual di Sekolah Menengah Atas - Aminah, Siti; Setiawan, Antonius Ian Bayu (Universitas Muria Kudus, 2021)
ABSTRACTThis study aims to develop the Short Movie “ASA” as a medium for guidance and counseling services to prevent sexual violence in high school. This research uses a Research and Development procedure by Borg and Gall. The result of this study is that the short movie is decent for preventing sexual violence in high school. Based on the material expert’s judgment, the short movie scored 94,4% in a decent category. Moreover, the media expert’s judgment scored 87,5 with a decent category. Field tests result on five school counselors also show 92,27%, which includes a decent category for using the short movie as a suitable medium. In conclusion, the short movie “ASA” is decent for media guidance and counseling services to prevent sexual violence in high school.